User-centered prosthetic development: Comprehension of amputees' needs - Christ, O.; Jokisch, M.; Preller, J.; Beckerle, Philipp; Wojtusch, J.; Rinderknecht, S.; Von Stryk, O.; Vogt, J. (Biomedizinische Technik, 2012)
The goal of user-centered development (UCD) is an active involvement of the user for a clear understanding of the users' needs. In the context of rehabilitation engineering it is essential to integrate the users' needs into the development meth-odology. In fact the use or disclaim of assistive device depends on good comfort and satisfaction during application. Es-pecially prostheses are developed to improve amputees' quality of life up to live independently again. UCD can improve integrating the amputees' needs into the prosthesis' properties. For a more detailed view of the prosthesis-users' needs we developed a questionnaire and collected data from patients regarding their needs using lower limb prostheses. 88 items, describing satisfaction, usability, appearance, functionality and handling of the prosthesis in different motor situa-tions, were generated. Among 65 participants, 29 transfemoral amputees and experienced prosthesis users completed the questionnaire. The results indicate a lack of satisfaction with the prosthesis shaft as well as with different motor func-tions. Furthermore, the majority feels socially restricted and is dissatisfied with their appearance in public. While the lat-ter is significantly negative correlated with feelings of social restriction, problems during changing gait speed are signifi-cantly negative correlated with feelings of certainty and stability during spontaneous movements. Although prostheses are developed to help to improve amputees' quality of life, the lack in different motor- and social- issues are noticeable. This indicates that the enhancement of changing gait speed in prostheses may help amputees to feel more certain and natural during walking. From an amputee's point of view, this could be one important predictor for being more satisfied and a first step for being more independent in life in general. With this first step of UCD, important information for the design of prosthesis in future has been generated. © 2012 by Walter de Gruyter Berlin Boston.
CRIS-Team Scopus Importer:2021-09-24